2016
DOI: 10.1186/s13054-016-1324-3
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of Candida biomarkers and DNA detection for the diagnosis of invasive candidiasis in ICU patients with severe abdominal conditions

Abstract: BackgroundTo assess the performance of Candida albicans germ tube antibody (CAGTA), (1 → 3)-ß-D-glucan (BDG), mannan antigen (mannan-Ag), anti-mannan antibodies (mannan-Ab), and Candida DNA for diagnosing invasive candidiasis (IC) in ICU patients with severe abdominal conditions (SAC).MethodsA prospective study of 233 non-neutropenic patients with SAC on ICU admission and expected stay ≥ 7 days. CAGTA (cutoff positivity ≥ 1/160), BDG (≥80, 100 and 200 pg/mL), mannan-Ag (≥60 pg/mL), mannan-Ab (≥10 UA/mL) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 37 publications
4
78
1
6
Order By: Relevance
“…PCR performance data for forms of IC other than candidemia are relatively limited -for intra-abdominal candidiasis, PCR sensitivities of 86-91% have been reported for the species targeted, but specificity varies widely (33-97%) Fortún et al, 2014;León et al, 2016;Clancy and Nguyen, 2018b). Nguyen et al (2012) found a Candida real-time PCR assay to be more sensitive than the Fungitell R 1,3-β-D glucan (BDG) assay (Associates of Cape Cod, United States) for diagnosis of all IC (80 versus 56%) as well as deep seated (blood culture negative) candidiasis (89 versus 53%).…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
“…PCR performance data for forms of IC other than candidemia are relatively limited -for intra-abdominal candidiasis, PCR sensitivities of 86-91% have been reported for the species targeted, but specificity varies widely (33-97%) Fortún et al, 2014;León et al, 2016;Clancy and Nguyen, 2018b). Nguyen et al (2012) found a Candida real-time PCR assay to be more sensitive than the Fungitell R 1,3-β-D glucan (BDG) assay (Associates of Cape Cod, United States) for diagnosis of all IC (80 versus 56%) as well as deep seated (blood culture negative) candidiasis (89 versus 53%).…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
“…In one study of 107 ICU patients, two or more serial BDG levels of 80 pg/ml in consecutive measurements obtained 24–48 hours apart resulted in a sensitivity of 80%, specificity of 75%, and strong negative predictive value of 95.9% (89.3%–98.5%) for candidemia . Multiple studies confirm improvement in BDG performance when serial measurements are used …”
Section: Evidence For Specific Novel Biomarkersmentioning
confidence: 98%
“…Given the potential for false positive results, some investigators have proposed serial BDG measurements and use in combination with other tests to improve performance for diagnosis of IC . In one study of 107 ICU patients, two or more serial BDG levels of 80 pg/ml in consecutive measurements obtained 24–48 hours apart resulted in a sensitivity of 80%, specificity of 75%, and strong negative predictive value of 95.9% (89.3%–98.5%) for candidemia .…”
Section: Evidence For Specific Novel Biomarkersmentioning
confidence: 99%
“…The diagnostic performance of several human proteins involved in the immune response against infection (other than antibodies) and inflammation has also been investigated in patients at risk for IC [61,65,103,[113][114][115]. In particular, procalcitonin (PCT), serum amyloid A (SAA), interleukin 17 (IL17), interleukin 23 (IL23) and transforming growth factor ß (TGF-ß), among other acute phase proteins and pro-inflammatory cytokines, have been reported as potential diagnostic biomarkers for IC [61,103,113,115]. However, these host-derived biomarker candidates have not yet proven to be sufficiently accurate to reach widespread clinical use on their own, nor have they been validated in large multicenter clinical studies [61,65,103].…”
Section: Other Human Proteinsmentioning
confidence: 99%